A Transpatellar Approach to Treat Distal Femoral Type C3 Fractures Combined with Patellar Fractures - Lee, Seung Hoo; Kim, Min Bom; Sim, Jae Ang; Han, Do Hwan (The Journal of Knee Surgery, 2018)
We report our surgical method used to treat type C distal femur fractures accompanied by patella fractures whereby we approach the articular surface of the femur through the already-fractured patella. We treated 10 patients with type C3 distal femur and patella fractures between May 2013 and April 2015. Because the patella was fractured in all cases, we could approach the articular surface of the distal femur through the transverse gap between the retracted patellar fracture fragments, “transpatellar approach.” Any surgical complications were recorded. Knee function was evaluated using the Böstman system. The average age of the 10 patients (8 males) was 42.9 years (range, 22.0–58.0 years). All distal femur fractures were type C3, combined with patella fractures. Bony union of the distal femur and patella was achieved in all but one patient, who required an additional bone graft (without any change in the implant). Overall, three patients (30%) reported excellent results and seven (70%) reported good results, based on the Böstman system. A midline anterior approach through a patella fracture adequately exposes the entire joint surface of the distal femur, except the posterior surface. This approach is useful when treating a type C distal femur fracture accompanied by a patella fracture. The level of evidence is IV.
Keywords: transpatellar approach; distal femur fracture; patellar fracture